FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT IMPOR KOMODITAS BERAS INDONESIA DAN DAMPAKNYA TERHADAP KESEIMBANGAN EKONOMI - Mahayu Mawar Kalista; Emia Rehulina BR Bangun; Balqis Sabila; Sandrina Dewi Lestari; Bagas Azhar Saputra (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
This study analyzes the factors influencing the level of rice imports in Indonesia and their impact on national economic balance. In the context of globalization and an open economy, Indonesia faces challenges in food security, particularly related to rice production and consumption. Data from the Central Bureau of Statistics (BPS) show fluctuations in rice imports from various countries during the period 2017-2023, with Thailand as the main supplier. The analysis indicates that domestic rice production, consumption, exchange rates, and local rice prices significantly affect import levels. Although rice imports can help stabilize prices and ensure food availability, negative impacts such as pressure on local farmers and trade balance deficits must also be considered. Government policies including import tariffs, quotas, and quality standards are crucial in managing imports and maintaining economic balance. This study employs a descriptive qualitative approach with secondary data analysis and literature review to provide a comprehensive understanding of the dynamics of rice imports in Indonesia.